2016
DOI: 10.1002/hec.3350
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Stability of Stated Preferences: The Case of Junior Nursing Jobs

Abstract: Summary With the growing use of discrete choice experiments (DCEs) in health workforce research, the reliability of elicited job preferences is a growing concern. We provide the first empirical evidence on the temporal stability of such preferences using a unique longitudinal survey of Australian nursing students and graduate nurses. The respondents completed DCEs on nursing positions in two survey waves. Each position is described by salary and 11 non‐salary attributes, and the two waves are spaced 15months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Our previous findings raise several questions for the current analysis of temporal stability by method of elicitation. As summarized above, we found that preferences for salary were unstable between the two cases of the DCE within the same wave (Yoo and Doiron 2013) and between the two waves of the same task (Doiron and Yoo 2017). In wave 1, salary was undervalued in the single-profile case task relative to the multi-profile case task.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Our previous findings raise several questions for the current analysis of temporal stability by method of elicitation. As summarized above, we found that preferences for salary were unstable between the two cases of the DCE within the same wave (Yoo and Doiron 2013) and between the two waves of the same task (Doiron and Yoo 2017). In wave 1, salary was undervalued in the single-profile case task relative to the multi-profile case task.…”
Section: Introductionmentioning
confidence: 67%
“…The temporal stability of preference estimates in the traditional multi‐profile case has been discussed more extensively in our previous work (Doiron and Yoo ). The results presented in table are consistent with our previous conclusions that, although preferences exhibit a high degree of stability across waves, salary stands out with the largest drop in its weight over time .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations